A practical model for predicting the dry shrinkage strain and creep coefficient of concrete containing graphene oxide nanosheets. Issue 3 (4th March 2023) - Mahmoodi, Mohammad Javad; Khamehchi, Masoumeh; Safi, Mohammad
Abstract : This paper has developed a semi-empirical model to evaluate the dry shrinkage strain and creep coefficient of concrete with graphene oxide nanosheets (GONs). The effect of adding GON on the dry shrinkage strain and creep coefficient is fully investigated. Also, the dependency of the dry shrinkage strain on the age when drying begins is carefully examined. Afterward, the results are compared with the results of available models which predict dry shrinkage strain and creep coefficient of common concrete and GON reinforced concrete. It is found that the developed model in this paper can fully predict the dry shrinkage stain and creep coefficient of concrete with GON. The predictions from the model are consistent with the most cited experimental measurements of dry shrinkage strain and creep coefficient of concrete containing GON. The outcomes of this investigation can pave the way to fabricate a sustainable concrete structure and achieve high-performance concrete.